Peran Human Capital dalam Pertumbuhan Ekonomi di Indonesia, Sebuah Analisis Deskriptif - Nazwa Akhaza Hani; Nikita Adelia Syafitri; Raihana Azzahra (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2025)
In an increasingly competitive era of globalization, the role of human capital has become the main focus of economic development in various countries, including Indonesia. Through descriptive qualitative analysis of various existing literature, this study is expected to provide a deeper understanding of the dynamics of the relationship between human capital and economic growth in Indonesia. The research shows that investment in education and health can drive economic growth, with high human capital going straight to the level of economic growth in Indonesia. Countries that align human capital development with labor market needs tend to benefit more.